2006
DOI: 10.1080/02640410500130854
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of an external focus of attention: Common coding or conscious processing?

Abstract: We conducted two experiments to assess the effect attentional focus has on learning a complex motor skill and subsequent performance under secondary task loading. Participants in Experiment 1 learnt a golf putting task (300 practice trials) with a single instruction to either focus on their hands (internal focus) or the movement of the putter (external focus). No group differences were evident during learning or retention. Differences between the groups were only apparent under secondary task load; the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
159
2
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 24 publications
11
159
2
13
Order By: Relevance
“…Wulf et al (1999) reported that the external focus of attention group was significantly more accurate during the chipping tasks than the internal focus of attention group during retention. Poolton et al (2006) also reported that the external focus of attention group significantly improved their putting accuracy during transfer testing, while the internal focus of attention group experienced a reduction in performance.…”
Section: Internal Versus External Focus Of Attentionmentioning
confidence: 98%
See 2 more Smart Citations
“…Wulf et al (1999) reported that the external focus of attention group was significantly more accurate during the chipping tasks than the internal focus of attention group during retention. Poolton et al (2006) also reported that the external focus of attention group significantly improved their putting accuracy during transfer testing, while the internal focus of attention group experienced a reduction in performance.…”
Section: Internal Versus External Focus Of Attentionmentioning
confidence: 98%
“…Eight studies compared the learning effects of altering the attention of golf practice session (see Table 1). These studies assessed the effect of implicit versus explicit learning (Bright & Freedman, 1998;Hardy, Mullen, & Jones, 1996;Kavussanu, Morris, & Ring, 2009;Masters, 1992;Maxwell, Masters, & Eves, 2000;Poolton, Masters, & Maxwell, 2005) or internal versus external focus of attention (Poolton, Maxwell, Masters, & Raab, 2006;Wulf, Lauterbach, & Toole, 1999) on golf performance.…”
Section: Attention During Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Nessa perspectiva, diversos estudos têm procurado investigar a influência do direcionamento do foco de atenção no processo de aquisição de habilidades motoras (PerkinsCeccato, Passmore, & Lee, 2003;Poolton, Maxwell, Masters, & Raab, 2006;Wulf, Hob, & Prinz, 1998;Wulf, Mcconnel, Gärtner, & Schwarz, 2002;Wulf & Su, 2007). Os resultados demonstram que as instruções que direcionam a atenção a um foco externo, tal como o efeito do movimento corporal no ambiente, produzem maior eficiência na aprendizagem quando comparadas ao uso da atenção direcionada a um foco interno (por exemplo, direcionar a atenção ao movimento do próprio corpo), na aquisição de habilidades motoras novas.…”
unclassified
“…Diferentemente, um foco externo, por exemplo, no efeito do movimento, promove o uso do processo automático (Poolton et al, 2006;Wulf & Su, 2007). Assim, uma dica simples, mas direta e objetiva, tal como uma frase curta e específica, uma informação visual ou palavra relevante à tarefa, pode reduzir a quantidade de informações e destacar um ponto a ser ressaltado no ambiente ou na própria tarefa, podendo reforçar a aprendizagem (Eversheim & Bock, 2002;Landin, 1994;Masser, 1993;Pasetto, Araújo, & Corrêa, 2006;Shim, Carlton, Chow, & Chae, 2005).…”
unclassified